The effect of 4% and 8% Thyme inclusion on the performance and health status of growing and finishing rabbit - Kustos, Károly; Abayné Hamar, Enikő; Balláné Erdélyi, Márta; Fazekas, Natasa; Heincinger, Mónika; Kovács-Weber, Mária; Nyíri, András; Szabó, Rubina; Zimborán, Ágnes; Gerber, Zsuzsanna; Gerber, Johann; Somodi, Brigitta (Animal welfare, Ethology and Housing Systems (AWETH), 2016)
During their post-separation period, the rabbits are most sensitive for digestive disorders, with increasing health risk. As growth promoter antibiotics are banned, so herbs and spices could be substitutes for those. In our experiments, whole plants of thyme were used in the feed mix with 5 and 10% dosage. According to our results the thyme added feed has a dose-dependent effect on the production of growing and finishing groups of rabbits. The health of the rabbits cannot be improved by the studied supplement, also mortality cannot be reduced. The season, depending also on the feed, influenced the production.
Keywords: Thyme; growth; mortality; season; herb